THE EXISTENCE OF CUSTOMARY LAW IN THE POLEMICS OF POSITIVE LAW â A STUDY FROM THE PERSPECTIVE OF CONSTITUTIONAL LAW - Saleh, M. (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
As a member of the law family, the Adat law is one form of positive law which plays particular role and contribution in the making process of the whole positive law in Indonesia. Existence of Adat law in the constitutional of Indonesia painted its own color. As one of the oldest customary law in the life of local community Adat law has become the seed and formatting idea of Indonesiaâs national law where Adat Law has widely influenced other positive law. Keywords: Adat Law.